Impact of a financial incentive on the completion of educational metrics - Pugh, Andrew (Int J Emerg Med, 2020)
BACKGROUND: The Accreditation Council for Graduate Medical Education (ACGME) requires all emergency medicine (EM) training programs to evaluate resident performance and also requires core faculty to attend didactic conference. Assuring faculty participation in these activities can be challenging. Previously, our institution did not have a formal tracking program nor financial incentive for participation in these activities. In 2017, we initiated an educational dashboard which tracked and published all full-time university faculty conference attendance and participation in resident evaluations and other educational activities. OBJECTIVES: We sought to determine if the implementation of a financially-incentivized educational dashboard would lead to an increase in faculty conference attendance and the number of completed resident evaluations. METHODS: We conducted a pre- and post-intervention observational study at our EM residency training program between July 2017 and July 2019. Participants were 17 full-time EM attendings at one training site. We compared the number of completed online resident evaluations (MedHub) and number of conference days attended (call-in verification) before and after the introduction of our financial incentive in June 2018. The incentive required 100% completion of resident evaluations and at least 25% attendance at eligible didactic conference days. We calculated pre- and post-intervention averages, and comparisons were made using a chi-square test. RESULTS: Prior to implementation of the intervention, the 90-day resident evaluation completion rate was 71.8%. This increased to 100% after implementation (p < 0.001). Conference attendance prior to implementation was 43.8%, which remained unchanged at 41.3% after implementation of the financial incentive (p = 0.920). CONCLUSIONS: Attaching a financial incentive to a tracked educational dashboard increased faculty participation in resident evaluations but did not change conference attendance. This difference likely reflects the minimum thresholds required to obtain the financial incentive.